The urban settlement in Kazakhstan: trends and factors - Dinmukhamed Zhumabaevich Iskaliyev (Наука. Инновации. Технологии)
Urbanization is one of the important socio-economic processes associated with deep structural division of the existing cities and causing significant changes in the economy and social life of the country. Thorough study of this process is of great scientific and practical importance. The article discusses the results of empirical research of urban settlement in Kazakhstan, on the basis of the analysis of the urban system of the country for conformity to the theoretical law rule of "rank - populous", also known as the Auerbach- Zipf law. The article also presents an overview of some modification of the Auerbach- Zipf law and considers the arguments of various authors to explain the causes of conformity and not conformity to the system of urban settlement patterns. According to the results of the analysis of the ranking of Kazakhstan's cities by population, and with analysis of Soviet censuses and two national censuses and current records (in 1989, 1999, 2009 and 2016), it was established that the transition to a market economy has not brought the expected changes in the urban system of Kazakhstan.